Perlindungan Hukum Hak Merek UMKM: Studi Lumpia Cenol Semarang - Arya Nurudin, Ikhsan Bintang; Santoso, Budi (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2025)
ABSTRACTVarious types of MSME products require legal protection, including food, beverages, and other products. One example is a traditional Semarang snack called Lumpia Cenol. This study aims to examine the legal protection for the trademark rights of MSME